Postmortem Increase in Body Core Temperature: How Inaccurate We Can Be in Time Since Death Calculations - Vojtíšek, Tomáš; Kučerová, Štěpánka; Krajsa, Jan; Eren, Bülent; Vysočanová, Petra; Hejna, Petr (The American journal of forensic medicine and pathology, 2017)
Postmortem increase in body core temperature is a well-known phenomenon in forensic practice. Despite this, cases of reliably documented postmortem hyperthermia are rarely reported in the forensic literature, and it is still not clear how frequently postmortem hyperthermia occurs and in which cases we may it predict. In routine forensic practice, the standard course of body cooling is expected, and the prediction of normal body core temperature in the time of death is used for back-calculating the time of death by Henssge method. The unexpected rising in body core temperature may considerably misguide the estimation of time since death in the early postmortem period. We present a rare case of nonviolent death in the hospital with exactly recorded unusual elevation of body core temperature after death, although the body temperature shortly before the death was normal. In the presented case, the "standard" cooling of the body began up to 4 hours after death.
Keywords: tělesná teplota; streptokokové infekce; Heart Failure; Time Factors; časové faktory; lidé; srdeční selhání; posmrtné změny; Skin Diseases, Bacterial; Streptococcus pyogenes; Male; Body Temperature; Aged; Streptococcal Infections; bakteriální nemoci kůže; Postmortem Changes; Fever; senioři; mužské pohlaví; horečka; Humans